Nutrition and health claims in products directed at children via television in Spain in 2012 - Miguel Ángel Royo-Bordonada; María José Bosqued-Estefanía; Javier Damián; Lázaro López-Jurado; María Ángeles Moya-Geromini (Elsevier, 2016)
Objective: To describe the use of nutrition and health claims in products directed at children via television in Spain and to analyse their nutrient profile. Methods: A cross-sectional study of television food advertisements over 7 days in five Spanish television channels popular among children. The products were classified as core, non-core or miscellaneous, and as either healthy or less healthy, according to the United Kingdom Nutrient Profile Model. We registered all claims contained on the product (packaging and labelling) and its advertisement. We calculated the frequency distributions of health and nutrition claims. Results: During the 420 hours of broadcasting, 169 food products were identified, 28.5% in the dairy group and 60.9% in the non-core category. A total of 53.3% of products contained nutrition claims and 26.6% contained health claims; 62.2% of the products with claims were less healthy. Low-fat dairy products were the food category containing the highest percentage of health and nutrition claims. Conclusion: Over half of all food products marketed to children via television in Spain made some type of nutrition or health claim. Most of these products were less healthy, which could mislead Spanish consumers.